Sustainable Remediation of Contaminated Soil Using Biosurfactants - Mulligan, Catherine N. (Frontiers in Bioengineering and Biotechnology, 2021)
Selection of the most appropriate remediation technology must coincide with the environmental characteristics of the site. The risk to human health and the environment at the site must be reduced, and not be transferred to another site. Biosurfactants have the potential as remediation agents due to their biodegradability, low toxicity and effectiveness. Selection of biosurfactants should be based on pollutant characteristics and properties, treatment capacity, costs, regulatory requirements, and time constraints. Moreover, understanding of the mechanisms of interaction between biosurfactants and contaminants can assist in selection of the appropriate biosurfactants for sustainable remediation. Enhanced sustainability of the remediation process by biosurfactants can be achieved through use of renewable or waste substrates, in situ production of biosurfactants and greener production and recovery processes for biosurfactants. Future research needs are identified.